1993
DOI: 10.1128/jvi.67.6.3384-3395.1993
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus precursor to terminal protein interacts with the nuclear matrix in vivo and in vitro

Abstract: The adenovirus precursor to the terminal protein (pTP), expressed in a vaccinia virus expression system or in native adenovirus, was assayed for its ability to interact with the nuclear matrix. Biochemical function was measured by determining the relative amount of pTP protein or of adenovirus DNA that remained associated with the nuclear matrix after extensive washing. pTP was retained on the matrix whereas 13-galactosidase was not, as assayed by quantitative immunoblot analysis. Nuclear matrix isolated from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 59 publications
2
34
0
Order By: Relevance
“…Targeting of the initial replicon is dependent on a dCMP modification of the preterminal protein (pTP), which enables pTP to form a complex with the DNA polymerase and the genome (Temperley and Hay, 1992). PTP mediates targeting of the heterotrimeric complex to the nuclear matrix (Fredman and Engler, 1993), possibly through an interaction with CAD (carbamyl phosphate synthetase, aspartate transcarbamylase and dihydroorotase) (Angeletti and Engler, 1998). Transcription and splicing are mediated by host proteins and viral RNA, and non-SNP RNA splicing factor, hnRNP C proteins, and RNA polymerase II all colocalize with viral RNA in nuclear inclusions.…”
Section: Structure and Location Of Nuclear Inclusions Formed During Amentioning
confidence: 99%
“…Targeting of the initial replicon is dependent on a dCMP modification of the preterminal protein (pTP), which enables pTP to form a complex with the DNA polymerase and the genome (Temperley and Hay, 1992). PTP mediates targeting of the heterotrimeric complex to the nuclear matrix (Fredman and Engler, 1993), possibly through an interaction with CAD (carbamyl phosphate synthetase, aspartate transcarbamylase and dihydroorotase) (Angeletti and Engler, 1998). Transcription and splicing are mediated by host proteins and viral RNA, and non-SNP RNA splicing factor, hnRNP C proteins, and RNA polymerase II all colocalize with viral RNA in nuclear inclusions.…”
Section: Structure and Location Of Nuclear Inclusions Formed During Amentioning
confidence: 99%
“…This is consistent with the observation that replication foci can only be clearly resolved from sites of ssDNA and dsDNA accumulation at later times of infection. Independently of the driving force, the viral genomes probably do not diffuse freely in the nucleus, since Ad DNA is tightly bound to the nuclear matrix throughout the course of infection (Schaack et al, 1990;Fredman and Engler, 1993). The sites of tightest attachment occur in the terminal fragments of the linear viral chromosome and are mediated by the viral terminal protein, which is covalently bound to the 5' end of each DNA strand (Schaack et al, 1990, Fredman andEngler, 1993).…”
mentioning
confidence: 99%
“…127 Ad terminal proteins also bind to the nuclear matrix, which is thought to assist transcription by anchoring the complexes at particular sites within the nucleus. 128 To assess the role of the DNA construct in transcription, a study involving nuclear microinjection of a viral genome versus plasmid DNA indicated that the genome led to 40% increased protein expression. 66 Though the authors hypothesized that nuclear decondensation is a greater factor in transcription than the DNA construct, the current understanding of lipoplex-mediated transfection disputes this, since DNA is believed to be released alone to the cytosol following lipoplex-mediated membranolysis.…”
Section: Gene Expressionmentioning
confidence: 99%